First records of Apatura ilia ([Denis & Schiffermüller], 1775) and Limenitis camilla (Linnaeus, 1764) in West Siberia - Svyatoslav A. Knyazev; Sofya M. Saikina; Vladimir Yu. Teploukhov; Pavel S. Sitnikov; Dmitry E. Galich; Oleg E. Kosterin (Acta Biologica Sibirica, 2024)
Two Nymphalidae species – Apatura ilia ([Denis & Schiffermüller], 1775) and Limenitis camilla (Linnaeus, 1764) are reported from the territory of West Siberia for the first time. At this moment we can observe the second wave of expansion of nemoral species of butterflies into Western Siberia from the European part of Russia. The driving factor of the range expansions discussed is no doubt the notorious global warming.